2014
DOI: 10.1128/jvi.01893-14
|View full text |Cite
|
Sign up to set email alerts
|

Expression Library Immunization Can Confer Protection against Lethal Challenge with African Swine Fever Virus

Abstract: African swine fever is one of the most devastating pig diseases, against which there is no vaccine available. Recent work from our laboratory has demonstrated the protective potential of DNA vaccines encoding three African swine fever viral antigens (p54, p30, and the hemagglutinin extracellular domain) fused to ubiquitin. Partial protection was afforded in the absence of detectable antibodies prior to virus challenge, and survival correlated with the presence of a large number of hemagglutinin-specific CD8 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(130 citation statements)
references
References 57 publications
9
112
0
1
Order By: Relevance
“…Experimental subunit vaccines based on a few of these antigens have generated different protective outcomes, demonstrating that these antigens do play some role in host protection. Immunization of animals with an expression library of restriction enzyme-digested ASFV genome fragments protected 60% of the animals (42). This outcome suggests that protection through subunit vaccines is feasible but is unlikely to be highly efficacious using a single or only a few antigens.…”
Section: Protein Expression By Constructs Encoding Asfv Antigensmentioning
confidence: 76%
“…Experimental subunit vaccines based on a few of these antigens have generated different protective outcomes, demonstrating that these antigens do play some role in host protection. Immunization of animals with an expression library of restriction enzyme-digested ASFV genome fragments protected 60% of the animals (42). This outcome suggests that protection through subunit vaccines is feasible but is unlikely to be highly efficacious using a single or only a few antigens.…”
Section: Protein Expression By Constructs Encoding Asfv Antigensmentioning
confidence: 76%
“…Other studies where pigs were immunised with OURT88/3 (Oura et al., 2005) suggested that although anti-ASFV antibodies were not enough to protect pigs, their role should not be completely ruled out. As for cellular immune responses, subsets of NK cells and CD8 + T-cells have been indicated to be relevant for protection induced by some live attenuated vaccine candidates (Scholl et al., 1989, Leitão et al., 2001, Oura et al., 2005, Lacasta et al., 2015) and DNA vaccines (Argilaguet et al., 2012, Lacasta et al., 2014). More specifically, in protected pigs immunised by oronasal route with ASFV NH/P68 isolate, cytotoxic activity was mediated by CD8 + cells which lysed macrophages infected with homologous isolates under restriction of class I swine leukocyte antigen (SLA) (Martins et al., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, immune responses elicited by DNA vaccines were variable and dependent on the fusion tag (i.e., soluble HA or ubiquitin) selected for ASFV recombinant antigen expression (Argilaguet et al, 2012). A recent study using an ASFV E75 expression library containing approximately 4000 individual plasmid clones (excluding p30, p54, and CD2v) demonstrated a correlation between protection and CD8+ T-cell response (Lacasta et al, 2014). Results from this study showed that the ASFV genome (∼170-190 kb) contains additional antigens with protective potential, and implied that identification of such determinants would enable advances in the development of protective subunit vaccine candidates.…”
Section: Introductionmentioning
confidence: 99%